Proposal of a new chemical marker for the quality control of the herb Scleromitrion diffusum - Zheng, Tao; Zhong, Chu-Chu; Yue, Grace Gar-Lee; Jiang, Dong-Min; Tong, Man-Ho; Wong, Hiu-Yan; Wong, Kwan-Ho; Wu, Meng-Hua; Lau, David Tai-Wai; Cao, Hui; Shaw, Pang-Chui; Lau, Clara Bik-San (Frontiers in Chemistry, 2025)
Baihuasheshecao (Scleromitrion diffusum (Willd.) R.J. Wang), a traditional Chinese medicinal herb, is extensively used as an ingredient in herbal teas and is a well-known folk medicine in China. However, two common adulterants, Hedyotis corymbosa (L.) Lam. and Hedyotis tenelliflora (BL.) Kuntze, belonging to the same family, are frequently mistaken as S. diffusum in folk medicine. This confusion has led to a growing concern about their identification and quality evaluation. While previous studies have demonstrated over 15 various compounds as potential chemical markers for authentication and quality control for S. diffusum, considering the selection criteria for chemical markers in the Chinese Pharmacopoeia, most of these compounds do not meet the pharmacopoeial requirements. Hence, this study aims to identify an appropriate chemical marker for S. diffusum based on thin layer chromatography (TLC) identification and high-performance liquid chromatography (HPLC) quality control, in order to differentiate from any counterfeits such as H. corymbosa and H. tenelliflora. Our findings suggested for the first time that the compound (E)-6-O-(p-coumaroyl) scandoside methyl ester which is specific to S. diffusum, could serve as the chemical marker. Here, attempt was made to establish standardized protocols for TLC identification, HPLC analysis, and quantitative methodologies, adhering to Chinese pharmacopoeial standards, along with laboratory scale preparation procedures. In conclusion, our findings have provided valuable insights to the identification and quality control processes for S. diffusum, and anticipated with potential applications by the industry and regulatory authority.